4(7x - 1) = 3(2x + 1) - 4(x + 6) solve for x

in Algebra 2 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

4(7x-1) =3(2x+1) -4(x+6)

28x -4 =6x +3 -4x -24

28x -6x +4x =4+3 -24

26x =-17

x=-17/26

x=-0.6538461
by

Related questions

0 answers
0 answers
asked Feb 26, 2013 in Algebra 2 Answers by anonymous | 232 views
1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
85,993 questions
91,890 answers
2,229 comments
23,907 users